Vegetables and fruit - Bauer, Andrea; Uter, Wolfgang; Szliska, Christiane (Kanerva's Occupational Dermatology, 2019)
Workers under risk are farmers, gardeners, bakers, pastry cooks, food handlers, cooks, and food processing industry workers. Skin symptoms in occupational food handling normally appear on the hands but may also develop on the face by direct skin contact or aerogen exposure. Clinical manifestations appear as irritant/allergic contact dermatitis, phototoxic/photoallergic contact dermatitis, contact urticaria (immunologic/non-immunologic), and protein contact dermatitis.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Allergy; Fruits; Irritation; Occupational contact dermatitis; Vegetables